Identification of Iron Ore Deposit in Sub-Surface Using Electrical Resistivity and Induced Polarization Methods in Nangabulik, Central Kalimantan - Rizki Alpiandi; Agus Budiono; Yanto Sudiyanto; Wahyu Hidayat (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2021)
Nangabulik, Lamandau Regency was one of the territories in Central Borneo that has potential for iron ore resources. A lot of geophysics methods can be used for exploration, among electrical resistivity and induced polarization methods. Then research is conducted to analyze the distribution model of resistivity and chargeability values in the subsurface, interpreting the location of iron ore based on resistivity and chargeability parameters, investigating alignment zone of iron ore deposit, and analyze the estimated total of iron ore resource. The configuration used is Wenner Alpha with 4 passes, each of which length is 235 m. Based on the 2D inversion result, resistivity and chargeability values were 21,15 – 96.153,51 Ωm and chargeability 23,6 – 542,58 ms. The iron ore deposit is to be found at GL-01, GL-02, and GL-04 tracks marked by resistivity value 614,22 – 5.803,90 Ωm and contrast in chargeability value around 212,32 – 542,58 ms. Large resistivity value due to porous between pebble–boulder iron ore fragments shape with pyroclastic rock grains filled the air. Based on the 3D model there was not found alignment zone of iron ore deposit at the research region. The total estimated deposit iron ore resource in the research region, at area ± 6 hectares is 41.036 tons.